Objective nationalism in Leo Brouwer ‘s characteristic dance: an analytical study through the Larue and Schenker´s theoretical proposals (2015)
The present paper exhibits an analysis of the characteristic Dance of Leo Brouwer through which both the dissimilar ways in which the Cuban composer involves archetypal elements of traditional music of his country, as the internal configuration of the music same. For this purpose, and after highlighting a brief overview of the popular music of this Antillean context, two concrete analytical proposals were used in an articulated way as operational theoretical references: the Jan LaRue category method and the Heinrich Schenker reductionist theory . In this sense, we believe that our study will allow an approach to the Brouwerian sound discourse from a different perspective than those found today, with which we hope to have contributed, in some way, to the study of said Latin American musical environment from the point of view of Systematic musicology as the main framework of understanding and reasoning.